Are collaborative care models in the primary care environment effective for improving depression outcomes and reducing mortality in elderly patients with depression?. Issue 10 (October 2017) - Howrey, Bret T.; Burke, Rebecca V.; Goldson, Tove M.; Sajan, Nida A.
Abstract : EVIDENCE‐BASED ANSWER : The answer is unclear. Collaborative care models combining primary care providers, care managers, and mental health specialists are effective in achieving small improvements in depression symptoms, remission, and recovery rates, and quality of life among adults of all ages (SOR: A, meta‐analysis of RCTs).